The Iron Rhine (IJzeren Rijn) arbitration (Belgium-Netherlands) award 2005 = L'arbitrage du "Rhin de Fer" (Belgique-Pays-Bas) sentence de 2005 - 12556 Permanent Court of Arbitration (The Hague, The Netherlands : Asser Press, 2007)
01